POTENSI EKSTRAK DAUN KETAPANG, MAHONI, DAN KERAI PAYUNG SEBAGAI BIOHERBISIDA TERHADAP Cyperus rotundus L. - Khairunnisa Khairunnisa; Indriyanto Indriyanto; Melya Riniarti (EnviroScienteae, 2018)
Bioherbicide is an alternative compound to control weeds which are environmentally friendly by utilizing parts of plant organs, like leaves that are applied in the form of extracts. The aim of this study is to determine the potential of Terminalia catappa, Swietenia macrophylla, and Filicium decipiens leaf extract as bioherbicides against Cyperus rotundus and to find out which leaf extract has the most effective to prevent the Cyperus rotundus growth. The study was done by using maceration techniques of leaf extract with ethanol solvent applied to Cyperus rotundus. This study was designed in a Completely Randomized Design (CRD) consisting of 4 treatments, which are control, 50% of Terminalia catappa leaf extract concentrate, 50% of Swietenia macrophylla leaf extract concentrate, and 50% of Filicium decipiens leaf extract concentrate. The results of this research showed that ketapang, mahogany, and kerai payung leaf extract could be used as bioherbicides because it has a very significant effect on inhibiting the height growth, the number of leaves, and the length of the roots of Cyperus rotundus. Filicium decipiens extract was the most effective extract in inhibiting the number of Cyperus rotundus leaves. However, each leaf extract did not significantly affect the reduction of chlorophyll content and dry weight. Therefore, further research is needed regarding the potential of these three leaf extracts to other weeds.